Mediating Role of CSR in the Relationship between Technology Adoption and MSMEs’ Financial Performance - Komang Widhya Sedana Putra P; NI Wayan Lasmi (Jurnal Economia, 2026)
Micro, small, and medium-sized enterprises (MSMEs) play a vital role in driving economic growth and resilience within the digital economy; however, sustaining strong financial performance remains a persistent challenge. This study explores the direct and indirect effects of artificial intelligence (AI) and Internet of Things (IoT) adoption on MSME financial performance, with corporate social responsibility (CSR) positioned as a mediating mechanism. Data were collected from 200 MSMEs operating in Bali and analyzed using partial least squares structural equation modeling. Findings indicate that AI and IoT adoption significantly enhance financial performance. Furthermore, CSR reinforces this relationship by improving operational efficiency, strengthening stakeholder trust, and supporting long-term sustainability initiatives. From an empirical perspective, the study provides new evidence on the combined role of advanced technologies and CSR in improving MSME outcomes. Theoretically, the research extends existing models by emphasizing CSR as a key link between technological innovation and business performance. Practically, the study offers relevant insights for MSME practitioners and policymakers seeking inclusive and resilient economic development.